2018
DOI: 10.3389/fphys.2018.00084
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Human Urinary Kallidinogenase Combined with Maixuekang Capsule Promotes Good Functional Outcome in Ischemic Stroke

Abstract: Aims: To evaluate the clinical efficacy of Human Urinary Kallidinogenase (HUK) and Maixuekang capsule in the treatment of acute ischemic stroke (AIS) patients.Methods: In this study, from January 2016 to July 2016, 60 patients with acute ischemic stroke were enrolled and 56 patients with complete information of whom 21 patients received HUK+ basic treatment (HUK group), 16 patients received HUK+ Maixuekang capsule + basic treatment (HUK+ Maixuekang group), 19 patients received basic treatment (control group). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 22 publications
0
16
0
Order By: Relevance
“…UK, a tissue kallikrein isolated from human urine, is a widely used drug for the treatment of ischemic stroke in China [11]. However, there is still no evidence for the role of UK play on inflammation and oxidative stress in model of migraine, which is a multifactorial neurodegenerative disease without satisfactory treatment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…UK, a tissue kallikrein isolated from human urine, is a widely used drug for the treatment of ischemic stroke in China [11]. However, there is still no evidence for the role of UK play on inflammation and oxidative stress in model of migraine, which is a multifactorial neurodegenerative disease without satisfactory treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Accumulated studies have reported the function of tissue kallikrein on antiapoptotic, antioxidant, and antiexcitotoxic properties, suggesting that tissue kallikrein could be an effective therapy for neurological disorders [10]. Human urinary kallidinogenase (UK) is a tissue kallikrein derived from human urine, cleaving kininogen to release bradykinin [11]. UK has been considered to be a positive regulatory substance in the kallikrein-kinin system by increasing kallikrein.…”
Section: Introductionmentioning
confidence: 99%
“…These include a study that randomized 200 patients with acute cerebral infarction after thrombolytic therapy, [25] a study of 58 patients with massive cerebral infarction treated with edaravone, [26] and a study of 47 patients with level 3 hypertension and ischemic stroke. [27] Another study looked at the treatment combination of urinary kallidinogenase with Maixuekang capsule and found that patients with ischemic stroke who received either urinary kallidinogenase in combination with standard treatment or urinary kallidinogenase in combination with standard treatment and Maixuekang capsule had significantly lower NIHSS scores after treatment than the control group. [27] A study using MRI to assess the effect of urinary kallidinogenase in patients with ischemic stroke found that alongside with observed improvements in stroke outcome, cerebral perfusion was enhanced and vascular endothelial growth factor (VEGF) and apelin expression were increased, suggesting a possible mechanism for the action of urinary kallidinogenase.…”
Section: Discussionmentioning
confidence: 99%
“…[27] Another study looked at the treatment combination of urinary kallidinogenase with Maixuekang capsule and found that patients with ischemic stroke who received either urinary kallidinogenase in combination with standard treatment or urinary kallidinogenase in combination with standard treatment and Maixuekang capsule had significantly lower NIHSS scores after treatment than the control group. [27] A study using MRI to assess the effect of urinary kallidinogenase in patients with ischemic stroke found that alongside with observed improvements in stroke outcome, cerebral perfusion was enhanced and vascular endothelial growth factor (VEGF) and apelin expression were increased, suggesting a possible mechanism for the action of urinary kallidinogenase. [27] These studies all show that further large-scale clinical studies into the use of AIS are needed, [28] but its use clinically shows a benefit to stroke outcome.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation